Penguatan Nilai Historis pada Motif Kerajinan Tangan Bambu Tirik (Arangan) dan Pembentukan Kelompok UMKM di Desa Pembakulan Kabupaten Hulu Sungai Tengah - Rianita; Damaiyanti, Varinia Pura; Fikri, Ahmad Fauzi; Bainah; Fadila, Della; Nobel, Johansson; Hawini, Medika Iri; Mikha; Tsabitha, Pasha Aulia; Aulia, Rahmadina Rizky; Aditiya, Rifky Bagus; Suan, Virginia Claudia Liwo (Prodi Sosiologi FISIP ULM, 2024)
Tirik bamboo is one of the natural potentials of the Dayak Meratus community and is a key element in handicraft arts, especially arangan which is rich in historical value. Weaving or arangan is part of the life of the Dayak Meratus community, arangan is a patterned weaving, while the plain one is called woven. The motifs listed in arangan not only have aesthetic value, but also connotative meaning. But unfortunately, the creativity in the artistic spirit of the Meratus community has not been utilized optimally. This is due to the lack of public knowledge about the promotion and marketing of arangan products, and the reduced interest of young people to continue the heritage of arangan art can threaten the preservation of woven bamboo tirik as the identity of the local wisdom of Pembakulan Village. With this, community empowerment with the live-in method through a participatory approach was carried out, directly involving local communities and government agencies. Activities were carried out starting from conducting socialization and workshops for product innovation and promotion. Followed by a Forum Group Discussion that focused on increasing women's participation in preserving local wisdom. The policy of a Decree (SK) on the formation of a creative weaving group through the Trade Office of Hulu Sungai Tengah Regency is the final result of the program. With the establishment of cooperation between basket craftsmen and the Hulu Sungai Tengah Trade Office, it can open up opportunities for wider access to product marketing, while encouraging product innovation, and improving the economic welfare of basket craftsmen.